Habitat selection, seasonal population changes, and behaviour of the Amsterdam Island fur seal Arctocephalus tropicalis on Gough Island - Nel, J.A.J. (University of Pretoria, 2022)
Thesis (DSc (Zoology))--University of Pretoria, 1977.